2004
DOI: 10.1091/mbc.e04-08-0715
|View full text |Cite
|
Sign up to set email alerts
|

Stress Granule Assembly Is Mediated by Prion-like Aggregation of TIA-1

Abstract: TIA-1 is an RNA binding protein that promotes the assembly of stress granules (SGs), discrete cytoplasmic inclusions into which stalled translation initiation complexes are dynamically recruited in cells subjected to environmental stress. The RNA recognition motifs of TIA-1 are linked to a glutamine-rich prion-related domain (PRD). Truncation mutants lacking the PRD domain do not induce spontaneous SGs and are not recruited to arsenite-induced SGs, whereas the PRD forms aggregates that are recruited to SGs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

63
988
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 897 publications
(1,084 citation statements)
references
References 60 publications
63
988
3
8
Order By: Relevance
“…28,31,32 Prion-like or low-complexity domains are often found in proteins affecting granule assembly. These domains are unusually common in proteins involved in RNA metabolism, and examples of proteins whose prion-like domain contributes to granule assembly include TIA-1/Pub1 in stress granules, 12,33 and Lsm4 in yeast P-bodies. 28 34 Recently, in vitro studies demonstrated that at sufficient concentrations, proteins containing prion-like domains such as FUS can assemble "hydrogel" structures, capable of interacting with other prion-like domains from a wide range of known mRNP granule proteins.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…28,31,32 Prion-like or low-complexity domains are often found in proteins affecting granule assembly. These domains are unusually common in proteins involved in RNA metabolism, and examples of proteins whose prion-like domain contributes to granule assembly include TIA-1/Pub1 in stress granules, 12,33 and Lsm4 in yeast P-bodies. 28 34 Recently, in vitro studies demonstrated that at sufficient concentrations, proteins containing prion-like domains such as FUS can assemble "hydrogel" structures, capable of interacting with other prion-like domains from a wide range of known mRNP granule proteins.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…Various heat shock proteins (HSPs) localize to, and affect, disassembly of stress granules in humans, flies, and yeast. 24,33,74,78 An appealing model 78 is that when cellular stress leads to accumulation of unfolded proteins, titration of HSPs would cause slower stress granule disassembly and trapping of mRNAs in nontranslating states, thus helping cells conserve resources. As HSPs become available again either via increased synthesis, or from having dealt with other unfolded proteins, stress granules could once more be disassembled.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…Comparisons among the cellular and misfolded properties of the known Q/N-rich domain are shown in Table 1 [20][21][22][23][24][25][26][27][28][29][30][31] . The cellularfolded Q/N-rich domain shared key properties characteristic of the misfolded proteins, including insolubility and a tendency to form aggregates via intrinsic element-and self-interactions.…”
Section: Functional Substitutions Of Tdp-43 C Terminus By Prion Domainmentioning
confidence: 99%
“…The RNA-binding domains of Tia1 recognize the U-and A-U-rich motifs in the 3 0 UTRs of mRNAs recruited into stress granules, 78 and the Q-rich region is required for the recruitment of Tia1 into stress granules, and alone forms protease-resistant polymers in the Hsp70-dependent manner in vivo. 111,112 In vitro, Tia1 forms fibers that, according to Congo Red and Thioflavine-T tests, as well as EM and X-ray analysis, have amyloid structure. 45,113 Moreover, a recent study in yeast demonstrated that full-length mouse Tia1 forms heritable SDS-resistant prion-like cytoplasmic aggregates that co-localize with P-bodies / stress-granules.…”
Section: Prions Amyloids and Mrna Turnovermentioning
confidence: 99%
“…118,119 In mammals, P-bodies contain fibrils of TNRC6A (GW182) 120 and DDX6 (RCK, p54) 121 proteins; both of which also have CBRs / LCRs. 120,121 Even though the presence of multiple amyloidogenic proteins with CBRs / LCRs in P-bodies and stress granules led to the hypothesis that functional amyloids are implicated in the biogenesis of these RNPs, 45,111,118,119 so far there is no proof that these proteins are present in RNPs in the amyloid state. 122 Indeed, it appears that initial formation of these RNPs is enthalpy driven, depends on multivalent interactions involving both CBRs/LCRs and RNAbinding domains of proteins and RNAs, and leads to the formation of large RNP complexes in extremely dynamic phase-separated liquidlike droplets.…”
Section: Prions Amyloids and Mrna Turnovermentioning
confidence: 99%